LETTER OF CREDIT (LC) DALAM PERSPEKTIF FIQH DAN ALTERNATIF LC DALAM BANK SYARI’AH - Jamaluddin Achmad Kholik (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2017)
Fiqh Islam has characteristics that are always relevant to be applied in every changing era, because it has a solution to the problematic mu`amalah contemporary. Letter of credit is one of conventional bank products in contemporary mu'malat which we need to study fiqh law, whether it can be justified syara 'or not. This article discusses the substance and application of the “Letter of Credit/ LC”, then reviewing on the fiqh law, because it is said in a rule